Simulación de la expresión matemática de un motor asincrónico para la visualización de las magnitudes eléctricas y físicas. - Naranjo Zumba, Henry Roberto (2021)
The industry is in continuous growth and updating of instrumentation equipment, especially in the control and maintenance of asynchronous motors in such a way that the need arises to visualize electrical quantities such as voltage and current and physical quantities such as speed and torque, the present document describes the mathematical expression of an asynchronous motor using Matlab® software to display the magnitudes of current, voltage, speed and torque, which are obtained by solving the Thévenin equivalent circuit in the transient regime and the transformation of Laplace we obtain the differential equations. Which allowed the calculation of the behavior of the engine in transitory regime, with or without load. It was demonstrated through the mathematical expression that the theoretical, experimental and simulated calculations correspond to the behavior of the asynchronous induction motor, which showed the graphs of the stator and rotor starting current. Thus, it was possible to make the prediction of the state of the equipment current variables according to its operation. The most important function of this mathematical expression was the practical demonstration of the behavior of the rotor starting current, which allowed the comparative analysis of the calculated and experimental values.